Temporal peculiarities of brittle fracture of rocks and concrete - Y. Petrov; I. Smirnov; A. Evstifeev; N. Selyutina (Fracture and Structural Integrity)
When we want to compare the strength of two materials, we compare the table values of quasistatic strength. However results of some experiments show that the strength ratio of the materials can change with increase in rate of loading. Such "substitution effect" of material strength at different strain rates is studied in this paper. It is shown that one material can have a lower dynamic strength for a higher static strength compared to the other material. Tests of two different materials, tests of mortar and concrete, and tests of concrete with different water content are considered. It is shown that load-carrying capacity of materials and the substitution effect of material strength in a wide range of loading rates can be predicted by the incubation time criterion.